Metropolitan delimitation in spatial perspective: selected Asian and European case studies - Kozak, Alicja (Delimitacja metropolitalna w perspektywie przestrzennej: wybrane studia przypadków z Azji i Europy, 2025)
Aim: The study aims to analyse and compare the various approaches to defining and delimiting metropolitan areas, with a specific focus on cases from the European Union and selected Asian countries (China and Japan). Methodology: The study applies a qualitative comparative analysis based on a comprehensive review of legal documents, statistical frameworks, and academic literature, supported by illustrative case studies from the European Union, China, and Japan. Results: The research identified key delimitation criteria, including administrative boundaries, commuting patterns, population thresholds, urban density, socio-economic interactions, urban sprawl, governance models, and levels of economic integration. It revealed that the European Union tends to apply more standardised frameworks, whereas Asian countries favour more flexible, context-specific practices. Implications and recommendations: The findings emphasise the complexity of achieving consistency in metropolitan delimitation, especially for cross-national comparisons and policy design. The study recommends adopting flexible and context-sensitive delimitation methods that reconcile governance needs with functional urban realities. Originality/value: The study contributes to the ongoing debate on metropolitan governance by highlighting how differences in delimitation approaches influence urban planning and socio-economic cohesion. It offers a nuanced perspective on the tensions between standardisation and contextual adaptation in urban policy frameworks.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 108-123
Keywords: metropolis; metropolitan delimitation; metropolia; delimitacja metropolitalna